Montenegro : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that Montenegro's recovery from the collapse of the lending boom in 2008 has been slowed by the debt overhang that remains in the private sector. Output contracted in 2012 because of unusually severe winter weather early in the year, as well as a sharp decline in aluminum production as the financial position of the troubled aluminum company (KAP) continued to worsen. Activity picked up in early 2013 as more favorable weather conditions resulted in a sharp increase in hydro-based electricity production. A sustained, multi-year fiscal consolidation effort is needed to reduce the public debt burden to an appropriately low level in the medium term.